Control of oxygen uptake during exercise - Poole, D. C.; Barstow, T. J.; McDonough, P.; Jones, A. M. (Medicine & Science in Sports & Exercise, 2008)
Other than during sleep and contrived laboratory testing protocols, humans rarely exist in prolonged metabolic steady states; rather, they transition among different metabolic rates (VO2). The dynamic transition of VO2 (VO2 kinetics), initiated, for example, at exercise onset, provides a unique window into understanding metabolic control. This brief review presents the state-of-the art regarding control of V[spacing dot above]O2 kinetics within the context of a simple model that helps explain the work rate dependence of VO2 kinetics as well as the effects of environmental perturbations and disease. Insights emerging from application of novel approaches and technologies are integrated into established concepts to assess in what circumstances O2 supply might exert a commanding role over VO2 kinetics, and where it probably does not. The common presumption that capillary blood flow dynamics can be extrapolated accurately from upstream arterial measurements is challenged. From this challenge, new complexities emerge with respect to the relationships between O2 supply and flux across the capillary-myocyte interface and the marked dependence of these processes on muscle fiber type. Indeed, because of interfiber type differences in O2 supply relative to VO2, the presence of much lower O2 levels in the microcirculation supplying fast-twitch muscle fibers, and the demonstrated metabolic sensitivity of muscle to O2, it is possible that fiber type recruitment profiles (and changes thereof) might help explain the slowing of VO2 kinetics at higher work rates and in chronic diseases such as heart failure and diabetes.